Impact of Air and Water Pollutant Emissions on Productivity Growth of Malaysia’s Manufacturing Sector - Ahmed, Elsadig Musa (2004)
The manufacturing sector has been the engine of growth for the Malaysian economy since the economic structural transformation in 1987. The sustainability of high economic growth depends on the productivity through the enhancement of total factor productivity. Total factor productivity development strategies emphasise on quality of the workforce, raw materials, capital structure and technical progress. The improvement and slowdown of total factor productivity (TFP) contribution to the manufacturing sector industries in terms of average annual growth rates depend on the quality of inputs used in the production of the manufacturing sector industries, that were reported to be of low quality and insufficient.